Enhancing Village Empowerment: Strategic Analysis of Using the Siskeudes Application in Bungah Village - Salam, Ubidas; Dzikrullah, Muhammad Tival; Febriyanti, Dika Putri; Adinata, Restu Eri (Journal of Office Administration : Education and Practice, 2023)
This study aimed to determine the application of the Siskeudes application in Bungah Village. The descriptive case study methodology is used in qualitative investigations. Data was collected through private practice, record keeping, and written interviews. Both primary and secondary data were collected. Including written interviews with selected informants and primary research data collected using the SISKEUDES application. Regarding secondary data, researchers found documents in Bungah Village containing information about the population, leadership structure, and past financial reports. Village financial management must be genuine, orderly, effective, and efficient before cash can be allocated. The Village Financial System application helps the community in its obligation to prepare financial reports (Siskeudes). Village officials had difficulty using the siskeudes application when it was implemented in Bungah Village. This study tries to identify the application of the SISKEUDES application in financial management considering the real limitations that occur in the field. Assistance and observation are used to carry out the implementation method which is then described qualitatively. As a result, the Siskeudes program facilitates villages for processing system-based financial reports, but their dissemination is limited by the competence of human resources and substandard village infrastructure. With proper use, this application can be an effective tool in supporting efforts to achieve sustainable development goals at the village level.